AN ANALYSIS OF BANJARESE AND DAYAK DEAH LANGUAGE - Noor, Maulida; Nisrina, Devie Dian; Ratnasari, Sri Endang; Yulinda, Anna; Sinuraya, Jusak Kencana; Misrita, Misrita (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2022)
This research aimed to measure how far the differences shown between the Banjarese and the Dayak Deah language. Then, it also to analyze the differences of phoneme between the two languages. It was quantitative approach that aimed to calculate how far the differences shown between the Banjarese and the Dayak Deah language, and combined with qualitative to analyze the differences of phoneme between them both. The research data were obtained from interview with a native speaker of the Dayak Deah tribe. The data that has been collected was analyzed using the dialectometric method. After calculated the data, the result was 90,5%. Thus, there were 181 differences and 19 equations of isolects between Banjarese and Dayak Deah language. It indicated that Banjarese and Dayak Deah had language differences. Moreover, they also had language equations and phoneme differences. The differences of phoneme divided into: (1) the differences of vowels which consist of: the changing of vowel in the final position and an additional vowel in the middle position, and (2) the differences of consonants which consist of: the changing of consonant in the initial position and additional consonant in the middle position, then the deletion consonant in the initial, middle, and final position.